2011
DOI: 10.1155/2011/724813
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Adalimumab in Canadian Patients with Moderate to Severe Crohn’s Disease: Results of the Adalimumab in Canadian SubjeCts with ModErate to Severe Crohn’s DiseaSe (ACCESS) Trial

Abstract: Adalimumab therapy induced and sustained steroidfree remission in both infliximab-experienced and anti-TNF-naive patients with moderate to severe CD. Clinically meaningful rates of fistula healing were also observed. Improvements in patient-reported outcomes were sustained throughout the 24-week study period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
2
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(85 citation statements)
references
References 30 publications
1
81
2
1
Order By: Relevance
“…Adalimumab therapy showed a sustained steroid-free remission and fistula healing in Canadian patients with moderate-to-severe CD (199).…”
Section: Oxidative Stress and Inflammation In The Gutmentioning
confidence: 92%
“…Adalimumab therapy showed a sustained steroid-free remission and fistula healing in Canadian patients with moderate-to-severe CD (199).…”
Section: Oxidative Stress and Inflammation In The Gutmentioning
confidence: 92%
“…Patients with CD who had received at least 1 dose of adalimumab during randomized placebo-controlled or open-label trials of adalimumab for the induction or maintenance of remission or mucosal healing (CLASSIC I and II, GAIN, CHARM, EXTEND, CARE, ACCESS, and a Japanese study) (11)(12)(13)(14)(15)(16)(17)(18)(19) or during the corresponding open-label long-term extension study (ADHERE) ( 20,21 ) were included. Patients who initiated therapy with placebo in any of the above studies were excluded, as our aim was to examine the added infection risk with combination therapy given that the current standard of care for the treatment of moderate-tosevere CD is a combination therapy or anti-TNF monotherapy ( 1 ), and due to relatively low duration of exposure to placebo in the data set, the number of infections that occurred in patients receiving placebo was too low for any meaningful assessment.…”
Section: Analysis Populationmentioning
confidence: 99%
“…CARE was a 20-week single-arm open-label study in Europe ( 16 ). ACCESS was a 24-week single-arm open-label study in Canada ( 17 ). Th e Japanese study had a blinded induction phase lasting up to 8 weeks, followed by a blinded 52-week maintenance phase, followed by an open-label extension phase lasting up to additional 184 weeks ( 18,19 ).…”
Section: Analysis Populationmentioning
confidence: 99%
“…Adalimumab, a fully human IgG1 monoclonal antibody to TNF-, was found to be effective in patients with CD refractory to conventional therapy and in patients with an attenuated response to infliximab [211,227,228]. Recent study showed that adalimumab could induce and maintain clinical remission in patients with moderate-to-severe UC as well, who did not have a satisfactory response to steroids or immunosuppressive agents [229].…”
Section: Inhibition Of Pro-inflammatory Cytokines 3211 Inhibitorsmentioning
confidence: 99%